Genetic Study Of Pocket A And B Domain Of RB1 Gene Among Malaysian Children With Retinoblastoma - Hanafi, Hanani Ahmad Yusof (2009)

(untitled)
Retinoblastoma (RB) is the most common intraocular tumor mainly affecting children under four years of age, with a prevalence of 1 in 15 000 to 20 000 live births. Retinoblastoma is divided into hereditary and non-hereditary types. The development of this malignancy requires both alleles of the tumor suppressor gene RB1 to be knockedout. Recent studies found mutation occurred more frequently in the pocket A and B domain of RB1 gene. The present study was undertaken to identify the mutation in the pocket A and B domain of RB1 gene among retinoblastoma patients in Malaysia, and the association of the mutation to the laterality and stage of the tumor.